Etos Kerja sebagai Landasan Staf Kantor Urusan Agama (KUA) dalam Bekerja: Studi Kantor KUA Kecamatan Licin, Banyuwangi Tahun 2023 - M As’adul Faizi; Lukman Hakim; Aniqotuzzuhro’ Fitriana (Medan Resource Center, 2023)
This article aims to discuss the work ethic as a basis for the staff of the Office of Religious Affairs at work (Office of Religious Affairs, Licin District, Banyuwangi in 2023). Within an institution, there are several objectives that can be summarized. The work ethic is one of the foundations that can improve the Office of Religious Affairs and the performance of staff at the Office of Religious Affairs at work. All employees of the Office of Religious Affairs must play an active role in improving the work ethic, a good work ethic of the staff of the Office of Religious Affairs can also have a good impact on the Office of Religious Affairs and the community. Work ethic is closely related to discipline, morale, honesty and responsibility. This study aims to determine the work ethic as the basis for the staff of the Office of Religious Affairs in their work. This research is a study of the Office of Religious Affairs. This study used the research technique of the Office of Religious Affairs with a descriptive type of research. Data collection methods used are interviews, observation and documentation. Data analysis in this study used triangulation techniques. The results of the research show that the work ethic that is applied includes several aspects 1). Aspects of work discipline in respecting time, 2). Honest aspects in terms of delivery and service to the community, 3). Aspects of service to the community by prioritizing the nature of friendliness, patience and familiarity with the community, 4). Aspects of responsibility in the field of work of each staff of the Office of Religious Affairs at work.